STATUS OF VILLAGE-OWNED LAND TRANSFER INTO THE DISTRICT GOVERNMENT ASSETS IN KINTAMANI BANGLI BALI - I Nyoman Prabu Buana Rumiartha (Jurnal IUS Kajian Hukum dan Keadilan, 2014)
The objective of the study is to determine the legal status, and factors inhibiting the transferof the villaged-owned land into the asset status of the Local Government in the sub-district ofKintamani Bangli Bali. This research employs empirical research method. The result of thestudy: the legal status of village-owned land transfer into local government assets based on the regulation for the village-owned land. The legal status of land comes from the customary law, while the land transfer regulation relates the state’s right to control the land for the purpose of public interest. The process of the village-owned land transfer into government assets seems to be based on the right to control the land for the purpose of public interest and the regional autonomy administration and decentralization.The provisions described in Article 2 paragraph (4) of Agrarian Law states that the state’s right to control can be delegated to the region and the customary community as required and is not in contradiction with the national interest, in accordance with the Government Regulation. The regulation serves as the basis for customary land administration. The factor hampering the transfer of village-owned land is the absence of legal product for land transfer and in this case is the absence of regional regulation. The external factor is that the land is the primary option for tourism development thus the legal certainty for its transfer has yet to exist..Keywords: Legal Status, Village-owned Land , & Local Government Asset.